LINTASAN PENGHIDUPAN (LIVELIHOOD TRAJECTORIES) DAN MIGRASI LINGKUNGAN DI DELTA MAHAKAM - Laksmi Rachmawati; Ade Latifa (Research Centre for Population, Indonesian Institute of Sciences, 2020)
The studies of environmental migration are still limited in Indonesia. Within the limited literature in the Indonesian context, Research Center for Population LIPI has conducted studies on environmental migration in 2015-2016 and the abandonment of shrimp pond due to migration in 2013 in Delta Mahakam, East Kalimantan. Using Livelihood Trajectories (LT) approach, this paper aims to examine the peopleâ€™s adaptation in Delta Mahakam related to environmental migration. The LT approach gives more understanding of the adaptation process that leads to migration decision-making. By applying a qualitative approach using interviews and focus group discussion (FGD), data are collected related to the changes of landscape livelihood and the adaptation to respond to it.Â The interviews and FGD conducted with farmers, fishers, aquaculture farmers who move or stay and with formal/informal leaders and patron. In the case of Delta Mahakam, migration becomes a strategy for adaptation. The decision to migrate is not an instant decision-making process but as a part of trajectories to sustain their livelihood.